105 One-day paediatric advanced trauma skills (PATS) course. (17th November 2016) - Martin, Rebecca; Martin, RM; Parikh, A
Abstract : Introduction: Following the success of the Barts Simulation 2-day PATS course which develops advanced paediatric trauma technical and non-technical skills specifically for senior clinicians, a 1-day multidisciplinary course was set up. The main focus was to target junior staff in the ED, Paediatrics and Anaesthetics who are looking to gain confidence on dealing with child trauma. Method: The course consists of 5 scenarios designed to examine both technical and non-technical skills associated with paediatric major hamorrhage, head injury, burns, drowning and polytrauma using the Laerdal Sim Junior. Scenarios were mapped to the eleven-point crisis resource management framework and our fully-immersive simulation centre provided the back-drop of a paediatric resuscitation room. Pre- post- course questionnaires were used to assess learning outcomes. Results: A pre-course survey of attendees ranging from ST1 – 6 trainees in EM and Paediatrics revealed that only 44.4% felt confident in assessment and management of an acutely injured patient as opposed to 70% of attendees on the two-day course which more commonly is attended by senior registrars and Consultants. Candidates expressed a desire to develop skills around knowing when to stabilise a patient before transferring to a Major Trauma Centre, gain experience in the use of anaesthetics drugs and fluids and develop a more structured and confident approach. Following the 1-day program the feedback confirmed 100% felt more confident in dealing with paediatric traumas. All attendees found the day challenging but mostly in a positive manner and this was quoted as being due to the realistic nature of the scenarios. The most common skills taken into practice from the course were teamwork, leadership, decision making, prioritisation and effective communication. Conclusion: The 1-day PATS course provides junior trainees with increased confidence in handling paediatric traumas and helps to develop non-technical skills to utilise in their day-to-day practice.